2008
DOI: 10.1007/s00423-008-0447-7
|View full text |Cite
|
Sign up to set email alerts
|

Is routine MR cholangiopancreatography (MRCP) justified prior to cholecystectomy?

Abstract: Although MRCP is diagnostically useful in the perioperative management in some cases, its routine use in the DRG-era may not be justified due to the costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…They conclude although MRCP is diagnostically useful in the perioperative management in some cases, its routine use in the DRG-era may not be justified due to the costs. 17 On the other hand Yan Qiu et al concluded the accuracy of preoperative ultrasonography for the diagnosis of associated CBD stones for patients with gallstones is not high and routine preoperative MRCP examination is suggested for patients with gallstones to rule out possible concomitant CBD stones. 18 The sensitivity and specificity in detection of CBD stone by MRCP in our study was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…They conclude although MRCP is diagnostically useful in the perioperative management in some cases, its routine use in the DRG-era may not be justified due to the costs. 17 On the other hand Yan Qiu et al concluded the accuracy of preoperative ultrasonography for the diagnosis of associated CBD stones for patients with gallstones is not high and routine preoperative MRCP examination is suggested for patients with gallstones to rule out possible concomitant CBD stones. 18 The sensitivity and specificity in detection of CBD stone by MRCP in our study was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Collins et al [6] reported that in nonjaundiced patients with normal duct son transabdominal ultrasound, the prevalence of CBD stone at the time of cholecystectomy is unlikely to exceed 5%. Considering the prevalence of silent CBD stone of 3%–5% [4561112] and the proportion of patients who might have visited other institutions in whom the diagnosis of CBD stones was potentially missed, our data do not show the prevalence of all retained CBD stones after laparoscopic cholecystectomy, only the prevalence of clinically significant retained CBD stones.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have even suggested the systematic use of MRCP in patients with acute cholecystitis to exclude CBDS [1,15,16] . Another option is EUS, an invasive test with a sensitivity of 93% and a specificity of 96% for detection of choledocholithiasis [14] but with a lower morbidity than ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have reported an incidence of common bile ducts stones (CBDS) from 9.1 to 16.5% of patients presenting with acute cholecystitis [1,2] , others did not find any relation between acute cholecystitis and choledocholithiasis [3] . A diagnosis of CBDS in these patients is a clinical challenge, since liver tests are already altered by the inflammatory process of the gallbladder [4] and the sensitivity of abdominal ultrasound (US) for choledocholithiasis detection is suboptimal [5,6] .…”
Section: Introductionmentioning
confidence: 99%